Race, rhetoric, and the postcolonial - Olson, Gary A., 1954-; Worsham, Lynn, 1953- (State University of New York Press, 1999)
"Race, Rhetoric, and the Postcolonial brings together six scholarly interviews with internationally renowned intellectuals outside of rhetoric and composition whose work has direct implications for scholarship within the discipline. Included are interviews with postcolonial theorist Homi Bhabha, postcolonial feminist and race theorist Gloria Anzaldua, African American race scholar Michael Eric Dyson, British cultural studies scholar Stuart Hall, Argentinean political theorist Ernesto Laclau, and French philosopher Chantal Mouffe."--Jacket